A realistic view of the Convention on the Rights of Persons with Disabilities - Ramos Pozón, Sergio (Acta Bioethica, 2017)
In this article, we critically analyze the Convention on the Rights of Persons with Disabilities. A realistic view should be taken into account when the text is applied in persons with mental illness. Two clinical situations will be revised in light of the Convention: informed consent and substitute decision-making. This interpretation states that the application of the Convention in Mental Health will respect satisfactory human rights of persons with disability.